Entrepreneurship Education and Economic Literacy Mediated by Entrepreneurial Self-Efficacy Affect Entrepreneurial Intention - Ummi Ainur Rizqi; Heri Pratikto; Heny Kusdiyanti (CV. AFDIFAL MAJU BERKAH, 2022)
After completing undergraduate studies, students will be faced with a competitive period to find work. The imbalance in the number of job seekers with available jobs causes an increase in the number of unemployed each year. The way to overcome these problems is to increase job opportunities by becoming entrepreneurs. However, changing the mindset from job seekers to job creators is a difficult challenge to face. Many studies have been conducted to determine the factors that influence entrepreneurial intentions. Several factors that influence the formation of entrepreneurial intentions are entrepreneurship education, economic literacy and entrepreneurial self-efficacy. This study aims to determine the direct and indirect effects of entrepreneurship education and economic literacy on entrepreneurial intentions mediated by entrepreneurial self-efficacy. This research was conducted on students of the Faculty of Economics and Business, State University of Malang who have taken entrepreneurship courses. The sample of this study was 245 with a total population of 1888 students obtained by collaboration of purposive sampling and proportional random techniques. The data analysis technique used statistical path analysis. The results of this study indicate that there is a significant positive direct effect of entrepreneurship education and economic literacy on entrepreneurial self-efficacy. The significant positive direct effect of entrepreneurship education, economic literacy, and entrepreneurial self-efficacy on entrepreneurial intentions. The significant positive indirect effect of entrepreneurship education on entrepreneurial intentions through entrepreneurial self-efficacy. The significant positive indirect effect of economic literacy on entrepreneurial intentions through entrepreneurial self-efficacy.